5.3.15 Problems 1401 to 1500

Table 5.313: Second order ode

#

ODE

Mathematica

Maple

6701

\[ {}y^{\prime \prime }+2 y^{\prime }-15 y = 0 \]

6703

\[ {}y^{\prime \prime }+6 y^{\prime }+9 y = 0 \]

6705

\[ {}y^{\prime \prime }-4 y^{\prime }+13 y = 0 \]

6706

\[ {}y^{\prime \prime }+25 y = 0 \]

6711

\[ {}y^{\prime \prime }-4 y^{\prime }+3 y = 1 \]

6712

\[ {}y^{\prime \prime }-4 y^{\prime } = 5 \]

6716

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = {\mathrm e}^{2 x} \]

6717

\[ {}y^{\prime \prime }+y^{\prime }-2 y = -2 x^{2}+2 x +2 \]

6718

\[ {}y^{\prime \prime }-y = 4 x \,{\mathrm e}^{x} \]

6719

\[ {}y^{\prime \prime }-y = \sin \left (x \right )^{2} \]

6720

\[ {}y^{\prime \prime }-y = \frac {1}{\left (1+{\mathrm e}^{-x}\right )^{2}} \]

6721

\[ {}y^{\prime \prime }+y = \csc \left (x \right ) \]

6722

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = \sin \left ({\mathrm e}^{-x}\right ) \]

6723

\[ {}y^{\prime \prime }+y = \csc \left (x \right ) \]

6724

\[ {}y^{\prime \prime }+4 y = 4 \sec \left (x \right )^{2} \]

6725

\[ {}y^{\prime \prime }-4 y^{\prime }+3 y = \frac {1}{1+{\mathrm e}^{-x}} \]

6726

\[ {}y^{\prime \prime }-y = {\mathrm e}^{-x} \sin \left ({\mathrm e}^{-x}\right )+\cos \left ({\mathrm e}^{-x}\right ) \]

6727

\[ {}y^{\prime \prime }-y = \frac {1}{\left (1+{\mathrm e}^{-x}\right )^{2}} \]

6728

\[ {}y^{\prime \prime }+2 y = 2+{\mathrm e}^{x} \]

6729

\[ {}y^{\prime \prime }-y = {\mathrm e}^{x} \sin \left (2 x \right ) \]

6730

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = x^{2}+\sin \left (x \right ) \]

6731

\[ {}y^{\prime \prime }-9 y = x +{\mathrm e}^{2 x}-\sin \left (2 x \right ) \]

6733

\[ {}y^{\prime \prime }+y = -2 \sin \left (x \right )+4 x \cos \left (x \right ) \]

6735

\[ {}y^{\prime \prime }+y^{\prime }+y = {\mathrm e}^{3 x}+6 \,{\mathrm e}^{x}-3 \,{\mathrm e}^{-2 x}+5 \]

6736

\[ {}y^{\prime \prime }-y = {\mathrm e}^{x} \]

6737

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = {\mathrm e}^{x}+{\mathrm e}^{2 x} x \]

6740

\[ {}y^{\prime \prime }+4 y = \sin \left (2 x \right ) \]

6741

\[ {}y^{\prime \prime }+5 y = \cos \left (\sqrt {5}\, x \right ) \]

6743

\[ {}y^{\prime \prime }-y = x^{2} \]

6744

\[ {}y^{\prime \prime }+2 y = x^{3}+x^{2}+{\mathrm e}^{-2 x}+\cos \left (3 x \right ) \]

6745

\[ {}y^{\prime \prime }-2 y^{\prime }-y = {\mathrm e}^{x} \cos \left (x \right ) \]

6746

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = \frac {{\mathrm e}^{2 x}}{x^{2}} \]

6747

\[ {}y^{\prime \prime }-y = x \,{\mathrm e}^{3 x} \]

6748

\[ {}y^{\prime \prime }+5 y^{\prime }+6 y = {\mathrm e}^{-2 x} \sec \left (x \right )^{2} \left (1+2 \tan \left (x \right )\right ) \]

6749

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+4 y = x +\ln \left (x \right ) x^{2} \]

6750

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }+2 y = \ln \left (x \right )^{2}-\ln \left (x^{2}\right ) \]

6753

\[ {}\left (1+x \right )^{2} y^{\prime \prime }+\left (1+x \right ) y^{\prime }-y = \ln \left (1+x \right )^{2}+x -1 \]

6754

\[ {}\left (2 x +1\right )^{2} y^{\prime \prime }-2 \left (2 x +1\right ) y^{\prime }-12 y = 6 x \]

6755

\[ {}x y^{\prime \prime }-\left (x +2\right ) y^{\prime }+2 y = 0 \]

6756

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 2 \]

6757

\[ {}\left (x^{2}+4\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 8 \]

6758

\[ {}\left (1+x \right ) y^{\prime \prime }-\left (2 x +3\right ) y^{\prime }+\left (x +2\right ) y = \left (x^{2}+2 x +1\right ) {\mathrm e}^{2 x} \]

6759

\[ {}y^{\prime \prime }-2 \tan \left (x \right ) y^{\prime }-10 y = 0 \]

6760

\[ {}x^{2} y^{\prime \prime }-x \left (2 x +3\right ) y^{\prime }+\left (x^{2}+3 x +3\right ) y = \left (-x^{2}+6\right ) {\mathrm e}^{x} \]

6761

\[ {}4 x^{2} y^{\prime \prime }+4 x^{3} y^{\prime }+\left (x^{2}+1\right )^{2} y = 0 \]

6762

\[ {}x^{2} y^{\prime \prime }+\left (-4 x^{2}+x \right ) y^{\prime }+\left (4 x^{2}-2 x +1\right ) y = \left (x^{2}-x +1\right ) {\mathrm e}^{x} \]

6763

\[ {}x y^{\prime \prime }-y^{\prime }+4 x^{3} y = 0 \]

6764

\[ {}x^{4} y^{\prime \prime }+2 x^{3} y^{\prime }+y = \frac {1+x}{x} \]

6765

\[ {}x^{8} y^{\prime \prime }+4 x^{7} y^{\prime }+y = \frac {1}{x^{3}} \]

6766

\[ {}\left (x \sin \left (x \right )+\cos \left (x \right )\right ) y^{\prime \prime }-x \cos \left (x \right ) y^{\prime }+y \cos \left (x \right ) = x \]

6767

\[ {}x y^{\prime \prime }-3 y^{\prime }+\frac {3 y}{x} = x +2 \]

6768

\[ {}\left (1+x \right ) y^{\prime \prime }-\left (3 x +4\right ) y^{\prime }+3 y = \left (3 x +2\right ) {\mathrm e}^{3 x} \]

6769

\[ {}x^{2} y^{\prime \prime }-4 x y^{\prime }+\left (9 x^{2}+6\right ) y = 0 \]

6770

\[ {}x y^{\prime \prime }+2 y^{\prime }+4 x y = 4 \]

6771

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = \frac {-x^{2}+1}{x} \]

6772

\[ {}y^{\prime \prime }+{y^{\prime }}^{2}+1 = 0 \]

6773

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+2 x y^{\prime } = \frac {2}{x^{3}} \]

6774

\[ {}x y^{\prime \prime }-y^{\prime } = -\frac {2}{x}-\ln \left (x \right ) \]

6776

\[ {}y y^{\prime \prime }+{y^{\prime }}^{3} = 0 \]

6777

\[ {}y y^{\prime \prime }+{y^{\prime }}^{2} = 0 \]

6778

\[ {}y y^{\prime \prime } = {y^{\prime }}^{2} \left (1-y^{\prime } \cos \left (y\right )+y y^{\prime } \sin \left (y\right )\right ) \]

6781

\[ {}y y^{\prime \prime }-{y^{\prime }}^{2} = y^{2} \ln \left (y\right ) \]

6782

\[ {}\left (x +2 y\right ) y^{\prime \prime }+2 {y^{\prime }}^{2}+2 y^{\prime } = 2 \]

6786

\[ {}2 \left (1+y\right ) y^{\prime \prime }+2 {y^{\prime }}^{2}+y^{2}+2 y = 0 \]

6876

\[ {}\left (1-x \right ) y^{\prime \prime }-4 x y^{\prime }+5 y = \cos \left (x \right ) \]

6879

\[ {}u^{\prime \prime }+u^{\prime }+u = \cos \left (r +u\right ) \]

6880

\[ {}y^{\prime \prime } = \sqrt {1+{y^{\prime }}^{2}} \]

6881

\[ {}R^{\prime \prime } = -\frac {k}{R^{2}} \]

6882

\[ {}x^{\prime \prime }-\left (1-\frac {{x^{\prime }}^{2}}{3}\right ) x^{\prime }+x = 0 \]

6888

\[ {}y^{\prime \prime }-6 y^{\prime }+13 y = 0 \]

6889

\[ {}y^{\prime \prime }+y = \tan \left (x \right ) \]

6898

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 0 \]

6908

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = 0 \]

6909

\[ {}2 y^{\prime \prime }+7 y^{\prime }-4 y = 0 \]

6910

\[ {}x y^{\prime \prime }+2 y^{\prime } = 0 \]

6911

\[ {}4 x^{2} y^{\prime \prime }+y = 0 \]

6912

\[ {}x^{2} y^{\prime \prime }-7 x y^{\prime }+15 y = 0 \]

6917

\[ {}y^{\prime \prime }+4 y^{\prime }+6 y = 10 \]

6925

\[ {}y^{\prime \prime }+2 y^{\prime }+4 y = 5 \sin \left (t \right ) \]

6927

\[ {}y^{\prime \prime } = f \left (x \right ) \]

6939

\[ {}x^{\prime \prime }+x = 0 \]

6940

\[ {}x^{\prime \prime }+x = 0 \]

6941

\[ {}x^{\prime \prime }+x = 0 \]

6942

\[ {}x^{\prime \prime }+x = 0 \]

6943

\[ {}y^{\prime \prime }-y = 0 \]

6944

\[ {}y^{\prime \prime }-y = 0 \]

6945

\[ {}y^{\prime \prime }-y = 0 \]

6946

\[ {}y^{\prime \prime }-y = 0 \]

6971

\[ {}y^{\prime \prime }+4 y = 0 \]

6972

\[ {}y^{\prime \prime }+4 y = 0 \]

6973

\[ {}y^{\prime \prime }+4 y = 0 \]

6974

\[ {}y^{\prime \prime }+4 y = 0 \]

6975

\[ {}y^{\prime \prime }+4 y = 0 \]

6976

\[ {}y^{\prime \prime }+4 y = 0 \]

6979

\[ {}2 y^{\prime \prime }-3 y^{2} = 0 \]

6986

\[ {}y^{\prime \prime }+9 y = 18 \]

6987

\[ {}x y^{\prime \prime }-y^{\prime } = 0 \]

6988

\[ {}y^{\prime \prime } = y^{\prime } \]

6996

\[ {}y^{\prime \prime }+y = 2 \cos \left (x \right )-2 \sin \left (x \right ) \]

6997

\[ {}y^{\prime \prime }+y = \sec \left (x \right ) \]